Cutting-edge science and socioscientific issues in science education - Μιχαηλίδη, Αιμιλία; Σταύρου, Δημήτρης (Education Sciences, 2017)
In the context of the EU project IRRESISITIBLE, five teachers in cooperation with science museums, research centers and researchers of Science Education developed a Nanotechnology module. In the next phase those teachers acted as multipliers and trained within learning communities, thirty two colleagues in the implementation of the module they developed and two other respective modules. At the end of each phase the participating students were called to develop exhibits according to the topic they had been taught. In this paper we investigate the possibilities and difficulties that arise during the development and wider-scale implementation of modules on cutting-edge and during the development of student-made exhibits on current scientific issues.